CRITICAL ENGAGEMENT AS A PARADIGM FOR LAY PARTICIPATION IN POLITICS - Raymond B. Aguas; Wilson Angelo G. Espiritu (Asian Horizons, 2015)
The laity are tasked with both engaging and improving the temporal sphere as well as evangelizing it. In complex matters, especially political ones, how is this task to be undertaken without compromising either the rightful autonomy of temporal affairs or one’s fidelity to the gospel? Furthermore, how is such a task to be undertaken in a world which is increasingly pluralistic and multicultural? In this paper, we argue against positions which would either completely unite faith and politics or totally separate them. We argue instead for Robert Benne’s model of Critical Engagement which allows the laity to engage temporal matters using secular disciplines without necessarily compromising their religious identity. Particular attention is paid to the situation in the Philippines where recent issues such as Reproductive Health or current issues like the legalization of divorce challenge the laity with the need for such critical engagement.